ESTUDO DE PROPRIEDADES TRIBO-MECÂNICAS DE SUPERFÍCIES DE TITÂNIO MODIFICADAS POR MÉTODOS FÍSICOS E QUÍMICOS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
Bioactive layers produced on titanium to induce osseointegration may not be mechanically stable and/or attend to the requirement for the bone-matching elastic modulus. The previous surface modification by ion nitriding can eventually improve adhesion and mechanical properties of such bioactive coatings. Titanium samples were DC plasma nitrided in low conditions of temperature (400 ºC and 600 ºC) and time (1 h and 3 h). Afterwards, Ca-P containing titania coatings were produced by anodic oxidation under the current density 150 m1-A/cm2 in the galvanostatic mode. The surfaces were studied by grazing-incidence X-ray diffraction, micro-Raman spectroscopy, Fourier-transform infrared spectroscopy, atomic force microscopy, scanning electron microscopy, energy-dispersive spectroscopy, instrumented indentation and nanoscratch tests. Effects of roughness and substrate on mechanical properties were corrected by means of analytical methods. The treatments at 600 ºC produced a stratified surface containing -TiN, -Ti2N and N-solid solution Ti(N), whereas the 673 K samples presented Ti(N) and evidence of nitride precipitates at a very shallow depth, as suggested by micro-Raman (depth of analysis ≤ 25 nm). The asperity degree and distribution increased with the treatment temperature and time. The most significant changes in the near surface hardness (5 to 15 GPa) and elastic modulus (170 to 200 GPa) profiles in respect to the pristine Ti were observed for 873 K treatments. However, the 673 K – 3 h sample presented scratch hardness twice as high as the substrate value, even if the ductile-like tribological response was preserved. Titania layers produced by anodic oxidation presented crystallographic phase anatase concomitantly with nitride compounds. The layers presented reduced brittleness under normal loading if grown on the previously nitrided surfaces, whereas elastic modulus profiles (75-90 GPa) were kept lower than bulk Ti and close to bone values (10-40 GPa). Because of the improved load bearing capacity,layers grown on Ti PN at 400ºC-3h presented critical load in scratch tests three times higher (~400 mN) than the control one (135 mN). We conclude hat Ti surfaces can be tailored by plasma nitriding to improve their load bearing capacity for deposition of bioactive layers.
Keywords: titânio; biomateriais; nitretação por plasma; oxidação anódica; propriedades mecânicas; espectroscopia Raman; titanium; biomaterials; plasma nitriding; Raman spectroscopy; mechanical properties; anodic oxidation; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA